Location selection, added value analysis, and financial feasibility of developing a non-smoking tobacco agroindustry in Jember District - Wardhana, Danu Indra; Putra Setiawan, Andika; Ayu Lestari, Shafira; Aulia, Anisa Nurina; Mananda, Afan Bagus (AGROMIX, 2025)
Introduction: Jember Regency is the largest tobacco producer in East Java, reaching 37,821 tons in 2022. Tobacco offers strong development potential and provides significant income for farmers, yet the industry faces challenges due to the health impacts of smoking. Developing non-cigarette tobacco agro-industries is a promising alternative, especially since tobacco waste remains underutilized. Therefore, this study aims to identify potential areas for the development of non-cigarette tobacco agro-industries in Jember Regency and evaluate products with the highest added value and feasibility. Methods: The Exponential Comparison Method (MPE) was used to determine the most suitable districts for agro-industrial development, while the Hayami Method assessed the added value of various tobacco-based products. Financial feasibility was analyzed using Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit-Cost Ratio, and sensitivity tests on changes in raw material prices and product selling prices. Results: Wuluhan District was identified as the most promising area. Added value analysis showed that biopellets generated the highest added value, with a profit percentage of 46.94% and IDR 28,750 added value. Financial analysis confirmed feasibility, yielding an NPV of IDR 9,728,771,339, an IRR of 68.75%, and a Net B/C ratio of 1.39 at a 6% interest rate. The break-even point was 45,720 units per year, with a payback period of 2.24 years. Sensitivity analysis showed feasibility even with raw material price increases up to 30%, while selling price decreases of up to 20% remained feasible; a 30% decrease made the project unfeasible. Conclusion: Wuluhan District is the most suitable area for developing non-cigarette tobacco agro-industries. Biopellets offer the highest added value and strong financial feasibility, providing economic and environmental benefits.